Role of A1c in the postpartum screening of women with gestational diabetes. (July 2013) - Benaiges, D.; Chillaron, J.J.; Pedro-Botet, J.; Mas, A.; Puig de Dou, J.; Sagarra, E.; Carrera, M.J.; Goday, A.; Flores- Le Roux, J.A.
Abstract Objective: This study aimed to determine whether A1c detects a different prediabetes prevalence in women with a history of gestational diabetes mellitus (GDM) compared to those diagnosed with oral glucose tolerance test (OGTT) and the influence of haemoglobin concentrations on A1c levels. Design and patients: We evaluated carbohydrate metabolism status by performing OGTT and A1c tests in 141 postpartum women with prior GDM in the first year post-delivery. Results: The overall prevalence of prediabetes was 41.8%. Prevalence of isolated A1c 5.7–6.4%, impaired glucose tolerance (IGT) and impaired fasting glucose (IFG) was 10.6%, 7.1%, and 9.2%, respectively. Isolated A1c 5.7–6.4% was associated with Caucasian origin (66.7% versus 32.6%, p = 0.02) and with higher LDL cholesterol concentrations (123 ± 28.4 mg/dl versus 101.6 ± 19.2 mg/dl, p = 0.037) compared with patients diagnosed by OGTT (IFG or IGT). Women with postpartum anaemia had similar A1c levels to those with normal haemoglobin concentrations (5.5% ± 0.6% versus 5.4% ± 0.4%, p = 0.237). Conclusions: Use of A1c in postpartum screening of women with GDM detected an additional 10.6% of patients with prediabetes and a more adverse lipid profile. Haemoglobin concentrations did not influence A1c values.